Where are my brothers? : The story of Dinah in Genesis 34 and women crying for help against sexual assault and rape in Eastern DR Congo - Kondemo, Marthe Maleke (Stellenbosch theological journal, 2022)
The Democratic Republic of Congo (DRC) has been called the "rape capital" of the world. For almost two decades, people in the east of Congo have suffered violent abuses including killings, mass rape, mutilations, sexual slavery, and abductions, committed by local armed forces, rebels, and civilians. Helpless women and girls are raped, while the society looks on. Rape culture is upheld by the absence or lack of enforcement of laws addressing violence against women and discriminatory laws. In Genesis 34, while Dinah's brothers are concerned and sympathise with their sister who has been raped by killing the rapist, Jacob kept silent. Approaching the text from a context of rape and sexual violence impunities against women, one is given the impression by the narrator that Jacob does not seem to be much concerned about his daughter's rape but is obsessed by his own reputation, while Dinah's two blood brothers desire for vengeance turns into excessive violence. If read from a bosadi womanhood perspective, Genesis 34 should stimulate the Congolese society to seek law enforcement strategies that would help reduce violence and end rape and sexual assault impunity against women. This article interrogates and examines the motives behind Jacob's inaction and Levi and Simeon's violent actions to challenge and outline the failures of the DRC system to support and care for women.